Решить это логарифмическое уравнение. подробно log2(x2 - 9) = log2(2 - х) + 1

Shkolяr Shkolяr    3   21.08.2019 20:30    0

Ответы
sasha60503 sasha60503  05.10.2020 10:06
Log2(x²-9) = log2(2-x)+1
log2(x²-9) = log2(2-x)+log2(2)
log2(x²-9) = log2(4-2x)
x²-9 = 4-2x
x²+2x-13 = 0
D = 4+13*4 = 56
√D = 2√14
x₁ = (-2-2√14)/2 = -1-√14
x₂ = (-2+2√14)/2 = √14-1

ОДЗ
x²-9 > 0
2-x > 0

x > 3
x < -3
x < 2

ОДЗ: (-∞; -3) ∪ (3; +∞)

√14-1 ≈ 2,7 ∉ ОДЗ
ответ: -√14-1
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра